The Merah Putih Village Cooperative-Based People's Economic Model: Institutional Strategy and Regional Policy for Sustainable Village Development - Cholifah, Anik Nur; Indarto, Tomi; Setyoningrum, Nilam Enggarsasi; Sukaris; Suwandi; Widiyawati, Wiwik (Yayasan Sinergi Kawula Muda, 2026)
Introduction: Strengthening the people’s economy is a key strategy in sustainable village development to reduce regional disparities and improve community welfare. The Merah Putih Village Cooperative (KDMP) serves as an institutional instrument to mobilize local economic potential through participation and independence. However, uneven institutional capacity, varying policy support, and limited integration with the local economy hinder its effectiveness. This study examines how institutional strategies and regional policies can optimize the role of village cooperatives. This study contributes by identifying a governance mechanism linking policy orchestration, capacity building, and ecosystem integration, and by proposing a replicable people-centered collaborative governance model that specifies actor roles, coordination mechanisms, and policy leverage points in the KDMP context. Methods: The study uses a qualitative descriptive-explanatory approach based on data from ten informants from five KDMPs and five local village government stakeholders. Data were collected through in-depth interviews, observations, documentation, and supporting questionnaires, and analyzed using thematic analysis to identify recurring institutional and policy patterns. Results: The findings indicate that although KDMPs have formal institutional structures, their effectiveness depends on managerial capacity, policy coordination, and integration within local economic networks. Novelty: These results suggest that strengthening cooperative performance requires not only improved governance but also alignment with the broader economic ecosystem. Contribution: This study offers theoretical insights into enhancing collaborative governance and practical guidance through measurable policy and institutional interventions.